Upregulation of programmed death ligand-1 in tumor-associated macrophages affects chemotherapeutic response in ovarian cancer cells. - Yong Soo Jang; Tae Wan Kim; Jae Sung Ryu; Hye Jeong Kong; Si Hyeong Jang; Gye Hyun Nam; Jae Hoon Kim; Seob Jeon (PLoS ONE, 2023)
To better understand the mechanism of chemoresistance in ovarian cancer cells, we aimed to investigate the influence of macrophages on the tumor cell response to carboplatin and identify the genes associated with chemoresistance. We mimicked the tumor microenvironment (TME) using a co-culture technique and compared the proliferation of ovarian cells with and without macrophages. We also examined M1 and M2 marker expression and the expression of key TME genes. Post the co-culture, we treated ovarian cancer cells with carboplatin and elucidated the function of programmed death-ligand 1 (PD-L1) in carboplatin chemoresistance. We investigated CD68 and PD-L1 expression in normal and cancerous ovarian tissues using immunohistochemistry (IHC). Finally, we analyzed the association between CD68 or PD-L1 expression and survival outcomes. Inducible nitric oxide synthase (iNOS) was downregulated, while the gene expression of M2 macrophage markers was increased in ovarian cancer cells. PD-L1, vascular endothelial growth factor (VEGF), Interleukin (IL)-6, IL-10, IL-12, signal transducer and activator of transcription 3 (STAT3), B-cell lymphoma 2 (BCL2), multidrug resistance 1 (MDR1), and colony stimulating factor 1 (CSF-1) were upregulated. Notably, PD-L1 was upregulated in both the ovarian cancer cells and macrophages. Ovarian cancer cells co-cultured with macrophages exhibited statistically significant carboplatin resistance compared to single-cultured ovarian cancer cells. PD-L1 silencing induced chemosensitivity in both types of co-cultured ovarian cancer cells. However, IHC results revealed no correlation between PD-L1 expression and patient survival or cancer stage. CD68 expression was significantly increased in cancer cells compared to normal or benign ovarian tumor cells, but it was not associated with the survival outcomes of ovarian cancer patients. Our study demonstrated that ovarian cancer cells interact with macrophages to induce the M2 phenotype. We also established that PD-L1 upregulation in both ovarian cancer cells and macrophages is a key factor for carboplatin chemoresistance.